O fenômeno da corrupção nos municípios do Maranhão: a violência estrutural, seus reflexos nos baixos índices de desenvolvimento humano e as possibilidades democráticas decorrentes do controle social formal - CASTRO, Sandro Rogério Jansen (2021)
This dissertation aims to understand the phenomenon of corruption in the municipalities of Maranhão, portrayed in the diversion of public funds and its connections with structural violence and the low human development index, as well as the need to change the paradigm of the criminal justice system to coping with the problem. The work is divided into a theoretical-critical study through the inductive methodological approach; the method of legal descriptive procedure and the research strategies used were documentary and bibliographic. The work is divided into three chapters. At first, corruption is contextualized in the current scenario to understand the crime of criminal responsibility of mayors under the aegis of Decree Law No. 201/67, as well as the breakdown of documentary data collected by the Federal Police and the correlation with the Human Development Index - HDI in Maranhão. Then, white-collar crime is objectively understood from the perspective of the critical paradigm of criminology. And, finally, the consequences of the diversion of funds revealed in structural violence and its effects on the low human development index are evaluated, as well as the need for the democratization of Criminal Law.